Burkina Faso, 2021 April Economic Update : Protecting the Poor During the Recovery and Beyond - World Bank (World Bank, Washington, DC, 2021)
According to latest estimates, the economy grew by 2.0 percent in 2020, 4 percentage points less than projected before the onset of COVID-19 (coronavirus). The primary sector grew by 5.2 percent, supported by strong performances of subsistence crops and cotton.. The tertiary sector, the largest component of the economy, contracted by 4.9 percent on account of COVID-19 social distancing measures. Inflation returned to positive territory in 2020 and closed the year above 4 percent. The pandemic had a positive impact on the external sector and a negative impact on the fiscal accounts. In 2020, the trade balance improved by 1.0 percentage point of GDP supported by historically high gold prices and low oil prices. The structurally negative services balance improved by 0.3 percentage points of GDP on account of cheaper electricity imports from neighboring countries. The fiscal deficit as a share of GDP reached 5.2 percent in 2020, an increase from 3.2 percent in 2019. Public debt stood at 47.6 percent of GDP by end-2020. Although many impacts of the COVID-19 shock persist, the economy is projected to continue its recovery in 2021. On the demand side, the recovery is supported by consumption and private investment. With security, humanitarian, health, and social challenges persistingthroughout the year, the fiscal deficit is projected to remain elevated at 5.2 percent of GDP. As concessional funding is finite and no other funding options are available, the Government will have to resort to more expensive borrowing in the regional market, which will shift the composition of the public debt stock towards a majority share of domestic debt.